Frequency of Preterm Delivery and Low Birth Weight in Patients with Gestational Hypertension - Shahida Munir, Najma Ghafar, Shehdost, Saba Nazir, Nazir Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the frequency of preterm delivery and low birth weight in patients with gestational hypertension. Study Design: Descriptive cross-sectional study Place and Duration of Study: Department of Obstetrics & Gynaecology, Bolan Medical Complex Hospital PGMI, Quetta from 1st April 2023 to 30th September 2023. Methodology: One hundred and five women suffering from gestational hypertension were enrolled. The outcomes of the pregnancy were assessed in terms of neonatal preterm birth, low birth weight presence. Frequency of preterm delivery and low birth weight was assessed and interpreted. The data regarding anthropometric measurements of the mother and child were carefully recorded. In addition to this, the frequency of maternal stress and its association with hypertension was also recorded. Results: The average maternal age was 26.8±6.1 years for the overall group, 26.1±6.3 years for the non-recurrent preeclampsia group, and 27.5±5.9 years for the recurrent preeclampsia group. The two groups had no significant difference in parity at index pregnancy (p=0.462). The mean body mass index at index pregnancy was 27.15±6.45 kg/m² in the overall group, 25.1±5.6 kg/m² in the non-recurrent preeclampsia group, and 29.2±7.3 kg/m² in the recurrent preeclampsia group. The majority of women had severe preeclampsia (58.09%), with a slightly higher percentage of recurrent preeclampsia cases (64%) compared to non-recurrent cases (52.72%). The average weight change was 12.1±15.2% for the overall cohort. The overall average weight change was 12.9±14.3%. Conclusion: The significance of maternal body mass index in predicting the outcomes of gestational hypertension, particularly recurrent preeclampsia, with preterm delivery and low birth weight. Keywords: Low birth weight, Pre-eclampsia, Gestational age, Pre-term delivery